Bof Blowing Process Challenges For High Rate Of Iron Ore Pellet Addition - Process Development And Results At Tkcsa - Daniel Augusto Godinho de Carvalho (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2017)
At thyssenkruppCSA, a positive heat balance at BOF process is faced, mainly because of low utilization of scrap and plant design. A singular logistic concept for hot metal transport between blast furnace and steel plant was established to optimize transportation and energy balance. Up to 80 kg of iron ore pellets/t steel is necessary for 340t BOF heat balance. In order to accomplish this challenge a stable blowing process, intensive operational development have been successfully executed: slopping rate reduction of 80% achieved without changing the blowing time. This paper describes steps and results of this development.